China's overcapacity delimma and how BRI can be an expedient resolution - Chen, Niyi (2019)
Since the reform and opening up, the Chinese economy has undergone a period of golden development, and various industries have grown rapidly. However, since the beginning of the 21st century, the Chinese economy has also begun to experience the problems that many fast-growing economies will encounter, that is, overcapacity. For China, the cause of overcapacity is not only the rapid increase in production capacity and the relatively low domestic demand but also its special economic and political grounds. Overheated investment from domestic and foreign investors, as well as blind industrial expansions, have together caused overcapacity, while local governments have adopted a tolerant or even incentive attitude towards it to maintain short-term sustained economic growth and keep up the employment. Therefore, the problem of overcapacity went worse. However, after Xi Jinping proposed the Belt and Road Initiative in 2013, this problem seems to have a solution. China began to transfer excess domestic production capacity to countries along the Belt and Road and negotiated with partner countries to carry out capacity cooperation. From a numerical point of view, the effect of this measure is indeed very significant, and it has been proved that the Belt and Road Initiative is admittedly an effective way to alleviate the problem of excess capacity in China. However, China's capacity problem is, after all, a structural difficulty of the domestic economy. If China’s economic policy does not truly change, the problem of overcapacity will remain obstinate. Therefore, whether the Belt and Road Initiative can fundamentally solve the problem of overcapacity is still an unknown.